Pencegahan Bullying dan Penguatan Kesehatan Mental Melalui Edukasi dan Konseling Fitrah: Pengabdian - Malim Soleh Rambe; Vitria Larseman Dela; Khairul Amri; Sukatno; Azijah Tussolihah Siregar; Eli Marlina Harahap; Ermaliza (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aims to prevent bullying and strengthen the mental health of elementary school students through holistic education and natural counseling. The background is the increasing psychosocial vulnerability of students due to social dynamics and limited mentoring services in schools. The method used is a descriptive participatory approach at Muhammadiyah Hutalambung Elementary School, South Tapanuli Regency, involving students in grades IV–VI and teachers. Activities include problem identification, anti-bullying education based on natural values, group natural counseling, integration of character values ​​in learning and extracurricular activities, and reflective evaluation. Data were collected through observation, reflection, and documentation, and analyzed qualitatively. The results show an increase in students' understanding of bullying, empathy, emotional regulation, and self-confidence. In addition, teachers experienced increased capacity in preventive and responsive mentoring, resulting in an inclusive, safe school climate oriented towards strengthening students' character and psychological well-being in a sustainable manner.